A Panoramic 3D Reconstruction System Based on the Projection of Patterns. (3rd April 2014) - Córdova-Esparza, Diana-Margarita; Gonzalez-Barbosa, José-Joel; Hurtado-Ramos, Juan-Bautista; Ornelas-Rodriguez, Francisco-Javier
This work presents the implementation of a 3D reconstruction system capable of reconstructing a 360-degree scene with a single acquisition using a projection of patterns. The system is formed by two modules: the first module is a CCD camera with a parabolic mirror that allows the acquisition of catadioptric images. The second module consists of a light projector and a parabolic mirror that is used to generate the pattern projections over the object that will be reconstructed. The projection system has a 360-degree field of view and both modules were calibrated to obtain the extrinsic parameters. To validate the functionality of the system, we performed 3D reconstructions of three objects, and show the reconstruction error analysis.